2015
DOI: 10.1590/s0100-204x2015000900007
|View full text |Cite
|
Sign up to set email alerts
|

Características de tolerância à seca em genótipos de uma coleção nuclear de arroz de terras altas

Abstract: Resumo -O objetivo deste trabalho foi avaliar características morfofisiológicas relacionadas à tolerância ao estresse hídrico em genótipos de uma coleção nuclear temática de arroz de terras altas, bem como identificar os materiais mais tolerantes. Foram avaliados 100 genótipos de arroz de terras altas em experimentos conduzidos com e sem estresse por deficiência hídrica. Os genótipos tenderam a aumentar o número de dias para o florescimento (FLO) e a diminuir a altura (ALT), na condição de estresse, mas manife… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0
3

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 15 publications
0
8
0
3
Order By: Relevance
“…DSI data confirm such differences in drought sensitivity between both cultivars, where BR 16 was more sensitive to WDR than Embrapa 48, while the opposite occurred in relation to WDV (Figure 2). Terra et al (2015) found high correlation between DSI and several traits of interest in rice (Oryza sativa L.), showing that this index can be efficient for selecting tolerant genotypes under water deficit conditions. Du et al (2009) used DSI to develop a soybean linkage map.…”
Section: Discussionmentioning
confidence: 93%
“…DSI data confirm such differences in drought sensitivity between both cultivars, where BR 16 was more sensitive to WDR than Embrapa 48, while the opposite occurred in relation to WDV (Figure 2). Terra et al (2015) found high correlation between DSI and several traits of interest in rice (Oryza sativa L.), showing that this index can be efficient for selecting tolerant genotypes under water deficit conditions. Du et al (2009) used DSI to develop a soybean linkage map.…”
Section: Discussionmentioning
confidence: 93%
“…The averages obtained for these variables were 11.23 cm and 0.89 g, respectively, and these averages were lower than those obtained in different studies with upland rice, cv. Spring (Cancellier et al, 2011;Terra et al, 2015).…”
Section: Resultsmentioning
confidence: 99%
“…Water stress due to lack of water affects the vegetative development of upland rice plants (Terra et al, 2015). The partial suppression of water supply to plants can trigger a series of morphological and physiological changes.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…O arroz de terras altas, comumente utilizado no ecossistema do cerrado, onde há possível ocorrência de verânicos, ou seja, ausência temporária de chuva durante a estação chuvosa, a cultura está sujeita a redução da produtitivade (Mendes et al, 2014;Terra et al, 2015).…”
Section: Introductionunclassified